Collective Security Treaty Organization Peacekeeping Specifics (2004-2010) - Manukyan, Zhak (YSU Journal of International Affairs, 2022)
The article refers to the legal basis of the Collective Security Treaty Organization (CSTO) peacekeeping, UN-CSTO cooperation issues in the peacekeeping sphere. An attempt has been made to examine the influence of military and political developments in the CSTO zone of responsibility on the further development of the CSTO collective security system (including CSTO Collective Peacekeeping Forces as its constituent part). In this context particular attention is paid to the CSTO policy towards the events in Kyrgyzstan in 2010.
Keywords: CSTO; UN; CSC; Kyrgyzstan; Russian Federation; agreement; peacekeeping; forces; mandate